2011
DOI: 10.1111/j.1399-3089.2011.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Which anti‐platelet therapies might be beneficial in xenotransplantation?

Abstract: Xenotransplantation could provide an unlimited and elective supply of grafts, once mechanisms of graft loss and vascular injury are better understood. The development of α-1,3-galactosyltransferase gene-knockout (GalT-KO) swine with the removal of a dominant xeno-antigen has been an important advance; however, delayed xenograft and acute vascular reaction in GalT-KO animals persist. These occur, at least in part, because of humoral reactions that result in vascular injury. Intrinsic molecular incompatibilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…Consequently, therapeutic intervention to prevent coagulation dysregulation in xenograft recipients will most likely encompass anti-platelet agents or the genetic engineering of the pigs to inhibit platelet activation and/or aggregation. Careful assessment of the fate of circulating platelets in xenograft recipients and their possible interaction with WBC will be needed to determine the anti-platelet agent of choice [11], thus inhibiting aggregation but minimizing the risk of bleeding, or the genetic manipulation that might be beneficial. Our group has reported that aggregation of platelets with WBC begins as early as day 2 in baboons after receiving pig kidney xenografts [1].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, therapeutic intervention to prevent coagulation dysregulation in xenograft recipients will most likely encompass anti-platelet agents or the genetic engineering of the pigs to inhibit platelet activation and/or aggregation. Careful assessment of the fate of circulating platelets in xenograft recipients and their possible interaction with WBC will be needed to determine the anti-platelet agent of choice [11], thus inhibiting aggregation but minimizing the risk of bleeding, or the genetic manipulation that might be beneficial. Our group has reported that aggregation of platelets with WBC begins as early as day 2 in baboons after receiving pig kidney xenografts [1].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of recombinant human antithrombin was clearly protective in the first week after pig-to-baboon renal xenotransplantation ( 98 ), but had no apparent long-term benefit in the pig-to-macaque renal model ( 142 ), even when combined with human activated protein C ( 143 ). Other reagents have also produced mixed results, and it would be reasonable to conclude that both genetic modification and pharmacotherapy will be necessary to fully control inflammation and coagulation in renal xenotransplantation ( 144 ).…”
Section: Preventing Kidney Xenograft Rejectionmentioning
confidence: 99%
“…In addition, Schmelzle et al. [9] discussed potential benefits of additional antithrombotic interventions in transgenic pigs and recent developments in pharmacological anti‐platelet therapy.…”
Section: Reviewsmentioning
confidence: 99%